Military technology and defense manpower - Binkin, Martin (Washington, D.C. : Brookings Institution, 1986)
This book reports the impact of emerging technologies and manpower to US armed forces. The book highlights some of the problem associated with the US army.
Includes index
Includes bibliographical references and index.
ii 18/01/2019
Loans
Keywords: Manpower; Technology; Technical education; United States